2014
DOI: 10.14260/jemds/2014/3193
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARATIVE STUDY OF THE EFFECT OF EPIDURAL BUPIVACAINE (0.125%) VERSUS EPIDURAL BUPIVACAINE (0.125%) AND BUTORPHANOL (2mg) FOR POST-OPERATIVE PAIN RELIEF IN LOWER ABDOMINAL AND LOWER LIMB SURGERIES

Abstract: BACKGROUND: Postoperative pain gives rise to various physiological and psychological phenomenons. Epidural analgesia with combination of local anesthetics and opioids provides better pain relief than local anesthetics alone in the postoperative period. Epidural opioids acting through the spinal cord receptors improve the quality and duration of analgesia along with dose-sparing effect with the local anesthetics. AIMS: The study was conducted to evaluate the efficacy of addition of opioids to local anesthetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Chaithanya K et al 25 Butorphanol (2 mg) was reported to achieve better quality of pain relief (lower VAS scores) and less nauseavomiting and slightly more sedation compared with tramadol (100 mg). Although, both butorphanol (2 mg) and tramadol (100 mg) as epidural adjuvant were effective for prolonging postoperative analgesia, a shorter duration of analgesia was noticed with butorphanol compared with tramadol; 5.35 ± 0.29 versus 6.25 ± 0.1.58 hours, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Chaithanya K et al 25 Butorphanol (2 mg) was reported to achieve better quality of pain relief (lower VAS scores) and less nauseavomiting and slightly more sedation compared with tramadol (100 mg). Although, both butorphanol (2 mg) and tramadol (100 mg) as epidural adjuvant were effective for prolonging postoperative analgesia, a shorter duration of analgesia was noticed with butorphanol compared with tramadol; 5.35 ± 0.29 versus 6.25 ± 0.1.58 hours, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Tramadolanditsmajormetabolitesareagonistatkappaopioidreceptorsandmixedagonist-antagonistsatmuopioid receptors. [3] Fentanyl, a highly lipid soluble, pure mu agonist with rapid onset and short duration of action has been used with various local anaesthetics for wide variety of surgicalprocedures.Fentanylishighlylipophilic,rapidlydiffusesout of epidural space and much of fentanyl analgesic effect is mediatedbysystemicabsorptionratherthanspinalreceptor binding. These highly lipid soluble agents as fentanyl are associated with rapid dermatomal spread, rapid onset and lowincidenceofpruritisornauseaandcanbepotentiatedby epinephrine.…”
mentioning
confidence: 99%